(untitled) (Journal of Global Accounting, 2024)
The study investigated the moderating effects of credit risk management proxy by capital adequacy ratio on the performance of commercial banks in Nigeria. Ex-post facto research design was adopted due to the deploy of quantitative and secondary data that are already public and cannot be altered. Utilising the census sampling techniques, a total of 13 Commercial Banks (CBs) listed on the Nigerian Exchange Group were sampled. Thus, the panel data obtained from the audited annual report of the sampled banks for the period 2010-2021, were analysed through the STATA version 16 software using Shapiro – Wilk and the general least square regression statistical tool. Findings made revealed that capital adequacy ratio has positive and significant effect on the financial performance (ROA) of CBs in Nigeria. The study also discovered that audit quality has no moderating effect on the relationship between capital adequacy ratio and financial performance in term of ROA of CBs in Nigeria. Based on the above findings, it was recommended that, commercial banks should effectively manage, monitor and improve their credit risk management strategies. Since it was concluded that credit risk management in terms of capital adequacy ratio has major effect on the financial performance of CBs in Nigeria. The regulators should also strengthen its monitoring capacity in this regard.